Threading the Concept: Powerful Learning for the Music Classroom - Hedden, Debra Gordon (Rowman & Littlefield Publishers, 2010)
This book provides both preservice and seasoned music educators with a unique and powerful way of teaching. The premise of the book is to offer a pedagogical approach that emphasizes focus on conceptual learning that is sensory oriented. From the musical concepts we teach_melody, harmony, rhythm, and form_the teacher targets one concept per lesson (e.g., melody), and provides learning experiences in singing, listening, performing, moving, reading/writing, and improvising/composing that are all focused on only that concept. Essentially, the learners are bombarded visually, aurally, and kinesthetically, gaining a firm grasp of the concept because they have heard, sung, moved, performed, written, and created in that class, all in small time segments. The teacher has a greater ability to reach all students' learning needs and engage them in active learning in each class. The book not only offers background information about the learning process, but also specific lesson templates that serve as conceptual models for music classes.